Room temperature fabricated ZnO thin film transistor using high-K Bi1.5Zn1.0Nb1.5O7 gate insulator prepared by sputtering - Kim, Il-Doo; Lim, Mi-Hwa; Kang, KyongTae; Kim, Ho-Gi; Choi, Si-Young (AMER INST PHYSICS, 2006)
In this letter, we report on dielectric and leakage current characteristics of room temperature deposited Bi1.5Zn1.0Nb1.5O7 (BZN) films on, the basis of crystallographic structure and suitability of BZN gate insulators as key building blocks in the fabrication of low voltage operating ZnO based thin-film transistors (TFTs). The BZN films exhibited a high dielectric constant (similar to 51) and good leakage current characteristics (similar to 10(-7) A/cm(2)) at an applied voltage of 5 V. All room temperature processed ZnO based TFTs using BZN gate insulator exhibited field effect mobility of 1.13 cm(2)/Vs and low voltage device performance less than 4 V. (c) 2006 American Institute of Physics.
Keywords: TA2O5